American fin-de-siècle materialism in Jesús López Pacheco's Ecólogas y Urbanas - Oliva Cruz, Juan Ignacio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The work of Jesús López Pacheco (1930-1997) has always been conscious of the environment surrounding his characters. It will be, however, in his last work during his lifetime, Ecólogas y Urbanas: Manual para evitar un fin de siglo siniestro (1996), where this concern is manifested in all its splendor. Behind this neologism (which combines “eclogue” and “ecology”) hides a lyrical activism that goes from personal to collective experience, and that tries to bring us back to sustainability as a paradigm for subsistence in the third millennium. From an ecological materialist perspective of North American origin, it analyzes human relations with other animal species, the critique of savage economic mercantilism and the environmental degradation of urban landscapes. Therefore, showing a sharp sense of humour linked with vis poietica, a possible postpastoral scenario is drawn, tinged with hope, as the only solution to humanity in the years to come.